Business Strategy Development Of Salted Fish Msmes Based On Business Model Canvas In Malabero Village, Bengkulu City - Mimi Kurnia Nengsih; Ade Tiara Yulinda; Meiffa Herfianti (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
Salted fish Micro, Small, and Medium Enterprises (MSMEs) in Malabero Village, Bengkulu City, play a significant role in the local economy. However, these businesses face challenges such as limited market reach, lack of innovation, inefficient production processes, and weak financial management. This study aims to analyze the current business model of salted fish MSMEs using the Business Model Canvas (BMC) framework and propose strategic improvements to enhance their competitiveness and sustainability.The research employs a qualitative approach, including field observations, interviews with business owners, and document analysis. The findings indicate that most MSMEs rely on traditional sales channels, lack product differentiation, and have minimal digital marketing adoption. To address these issues, this study suggests several strategic developments: (1) market expansion through digital platforms and retail partnerships, (2) product innovation with better packaging and value-added variants, (3) adoption of modern processing technologies to improve efficiency, and (4) improved financial management and access to funding.By implementing these strategies, salted fish MSMEs in Malabero Village can strengthen their market position, increase profitability, and ensure long-term sustainability. The study provides practical recommendations for business owners, policymakers, and industry stakeholders to support the growth of the salted fish sector in Bengkulu City.